Les maréchaux et les généraux napoléoniens - Jean-René Aymes (Mélanges de la Casa de Velázquez)
This comparative study is a mere outline, intended as an invitation to anyone interested in pursuing the subject further. The article takes a brief look at Soult, Suchet and several governors of Catalonia. This approach, based largely on an examination of archives in Paris, looks at the reputations of marshals and generals, their less-than-honourable private conduct, their disagreements, their tense relations with king Joseph Bonaparte, their assessment of the situation, their concept of pacification and their methods of combating the guerrilla. It appears that Suchet, and to a lesser extent also Thiébault and Duhesme, opted for less brutal methods and a more enlightened style of administration than those advocated or put into practice by Soult, Sébastiani or Dorsenne. Most of the confidential information reported to Paris tends to show that the marshals and generals refused to settle their differences and were aware that they faced practically insurmountable difficulties.